Content analysis of instagram posts related to the performance of the national search and rescue agency in early 2021 - Susilo, Daniel; Putranto, Teguh Dwi (Jurnal Komunikasi Profesional, 2021)
Various disasters that occurred in Indonesia in early 2021 occurred in a row, starting from earthquakes, landslides to floods in various regions in Indonesia, and the National Search and Rescue Agency (BASARNAS) increasing. This research aims to find out the Instagram post @sar_nasional performance of BASARNAS during the disaster that occurred in Indonesia in early 2021. The content analysis method is used as the research method with the unit of analysis in posts on Instagram @sar_nasional from January 1 to January 15, 2021. The conclusion obtained in this study is that the posts on Instagram @sar_nasional lead to more content posts about BASARNAS's performance in the @sar_nasional Instagram post-BASARNAS participation in the Sriwijaya SJ-182 plane crash from Jakarta to Pontianak than the disasters that occurred in several places in Indonesia.Keywords:Â Content Analysis; Posts; Instagram; Performance; BASARNAS.